Xanthine Oxidase Inhibitor, Allopurinol, Prevented Oxidative Stress, Fibrosis, and Myocardial Damage in Isoproterenol Induced Aged Rats. (7th June 2015) - Sagor, Md. Abu Taher; Tabassum, Nabila; Potol, Md. Abdullah; Alam, Md. Ashraful
Abstract : We evaluated the preventive effect of allopurinol on isoproterenol (ISO) induced myocardial infarction in aged rats. Twelve- to fourteen-month-old male Long Evans rats were divided into three groups: control, ISO, and ISO + allopurinol. At the end of the study, all rats were sacrificed for blood and organ sample collection to evaluate biochemical parameters and oxidative stress markers analyses. Histopathological examinations were also conducted to assess inflammatory cell infiltration and fibrosis in heart and kidneys. Our investigation revealed that the levels of oxidative stress markers were significantly increased while the level of cellular antioxidants, catalase activity, and glutathione concentration in ISO induced rats decreased. Treatment with allopurinol to ISO induced rats prevented the elevated activities of AST, ALT, and ALP enzymes, and the levels of lipid peroxidation products and increased reduced glutathione concentration. ISO induced rats also showed massive inflammatory cells infiltration and fibrosis in heart and kidneys. Furthermore, allopurinol treatment prevented the inflammatory cells infiltration and fibrosis in ISO induced rats. In conclusion, the results of our study suggest that allopurinol treatment is capable of protecting heart of ISO induced myocardial infarction in rats probably by preventing oxidative stress, inflammation, and fibrosis.